UMP students travel to Banda Aceh to help orphans - Nik Naizi, Husin (The Star Publications (M) Berhad, 2016)
Banda Aceh: Some 230 orphans here received aid from Universiti Malaysia Pahang (UMP) as part of its corporate social responsibility programme.